Homolateral Lisfranc Dislocation 1-5 in a Collegiate Quarterback: A Case Study - Steven R. Dayton BA; Kurt M. Krautmann MD; Michael J. Boctor BA; Vehniah K. Tjong MD; Anish R. Kadakia MD (SAGE Publishing, 2021)
Background: Lisfranc injuries encompass a spectrum of injuries to the tarsometatarsal (TMT) joint complex from ligamentous sprains to fractures with dislocation. While studies have shown it is possible to return to sport (RTS) after low-energy injuries, no literature exists demonstrating RTS after homolateral fracture/dislocation of all 5 metatarsals. Indications: We present a novel technique for repair of homolateral Lisfranc fracture/dislocation of metatarsals 1-5 which may be used in high-level athletes attempting to return to competition. Technique Description: A dual approach is utilized, with a dorsal approach to allow for fusion of the 2nd and 3rd TMT joints and medial approach for internal bracing of the 1st TMT joint. The 2nd and 3rd metatarsals were denuded of all cartilage and the fusion site was fully prepared. Rigid fixation was applied to the fusion sites and then stability of the 1st TMT was reassessed. A guidewire for the cannulated InternalBrace (Arthrex; Naples, FL) system is initially inserted into the base of the 1st metatarsal. Positioning is confirmed with fluoroscopic imaging and the 3.4 mm drill is passed over the wire, followed by the cannulated tap. A 4.75 mm SwiveLock anchor (Arthrex; Naples, FL) with FiberTape suture (Arthrex; Naples, FL) is then inserted into the metatarsal base. The guidewire is placed in a reciprocating position on the medial cuneiform. The 2.7 mm drill is passed over the wire, followed by the 3.5 mm tap. A 3.5 mm SwiveLock anchor is then loaded with the FiberTape suture from the 1st metatarsal. Tensioning is performed, and the 3.5 mm SwiveLock anchor is inserted into the medial cuneiform. Results: The athlete was cleared to return to full competition 9 months following surgery. Physical examination demonstrated stability in dorsiflexion and abduction. Both weight-bearing x-rays and computed tomography scans showed no evidence of hardware failure, no instability of the 1st TMT joint, and solid fusion of the 2nd and 3rd TMT joints. Discussion/Conclusion: Current literature demonstrates that RTS is possible for athletes suffering from low-energy Lisfranc injuries. This novel surgical technique is the first to demonstrate return to sport of a high-level athlete from homolateral fracture/dislocation of all 5 metatarsals.